Epidemiology of infectious skin disorders among out patient in a tertiary care hospital, Srinagar, Uttarakhand - Deepak Dimri; Venkatashiva reddy B; Amit Kumar Singh (International Journal of Medical Research and Review, 2016)
Background: The epidemiology of skin morbidity in an area depends on climate, geography, socio economic status, nutrition, genetic and habits of the community. The objective of the present study was to describe the morbidity profile of infectious disease of the skin and subcutaneous tissue patients attending dermatology outpatient department in a tertiary care centre of Garhwal hills, north India.Methodology: It is a record based study done using the morbidity registers maintained for outpatients at dermatology department, HNB hospital, VCSGGMS&RI, Uttarakhand, North India.Results: The totals of 47465 new episodes of illnesses were treated in the skin outpatient department during 2009-14. 15481 (32.6%) patients presented with infections of the skin and subcutaneous tissue. Males and females were nearly equal. Overall the fungal infections of the skin and subcutaneous tissue were the most common (35.8%) followed by scabies. Viral diseases of skin, bacterial diseases of skin and tenia versicolor were most commonly encountered.Conclusion: This information will help in planning customize health services for patients health care.